2023
DOI: 10.1038/s43705-022-00209-1
|View full text |Cite|
|
Sign up to set email alerts
|

Ecological insights into soil health according to the genomic traits and environment-wide associations of bacteria in agricultural soils

Abstract: Soil microbiomes are sensitive to current and previous soil conditions, and bacterial ‘bioindicators’ of biological, physical, and chemical soil properties have considerable potential for soil health assessment. However, the lack of ecological or physiological information for most soil microorganisms limits our ability to interpret the associations of bioindicators and, thus, their utility for guiding management. We identified bioindicators of tillage intensity and twelve soil properties used to rate soil heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 83 publications
1
8
0
Order By: Relevance
“…Increased weighted mean predicted 16S gene copy number under tillage (Fig. 6) was also noted in a recent global metanalysis (Wilhelm et al, 2023), and is consistent with the idea that pulses of resources (e.g., C liberation or litter incorporation via tillage) select for competitors with fast growth potential in soil bacteria (Schmidt et al, 2018). These studies also found that larger mean estimated genome size correlated with lower soil health ratings and tillage, indicating a need for higher metabolic and regulatory capabilities under environmental instability (Schmidt et al, 2018; Wilhelm et al, 2023).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Increased weighted mean predicted 16S gene copy number under tillage (Fig. 6) was also noted in a recent global metanalysis (Wilhelm et al, 2023), and is consistent with the idea that pulses of resources (e.g., C liberation or litter incorporation via tillage) select for competitors with fast growth potential in soil bacteria (Schmidt et al, 2018). These studies also found that larger mean estimated genome size correlated with lower soil health ratings and tillage, indicating a need for higher metabolic and regulatory capabilities under environmental instability (Schmidt et al, 2018; Wilhelm et al, 2023).…”
Section: Discussionsupporting
confidence: 86%
“…We also found relative enrichment of Sphingomonas and Geodermatophilus under tillage, both of which have been identified as key tillage responders (Wilhelm et al, 2023). Under no-tillage, we also found enrichment of the genus Gaiella , ( Actinobacteria), which was one of several identified bioindicators of high biological soil health ratings (Wilhelm et al, 2023). We also found enrichment of anaerobic taxa (e.g., Anaerolineae ) (Yamada and Sekiguchi, 2020) in microaggregates (Fig.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Further work should focus on culturing and rigorously testing plant growth promoting effects of these taxa. Both of these taxa we were also recently identi ed as potential bioindicators of soil health (Wilhelm et al 2022(Wilhelm et al , 2023. In this case, rather than directly in uencing plant height they may just be indicating soil microsite variation that is favorable to plant growth.…”
Section: Actinobacterial Otus Correlate With Plant Heightmentioning
confidence: 95%